An eco-designed paper-based algal biosensor for nanoformulated herbicide optical detection - Scognamiglio, Viviana; Antonacci, Amina; Arduini, Fabiana; Moscone, Danila; Campos, Estefania V. R.; Fraceto, Leonardo Fernandes [UNESP]; Palleschi, Giuseppe (Elsevier, 2019)
In this study we reported the development of a paper-based algal biosensor for the optical detection of nanoencapsulated-atrazine, a forefront nanoformulated herbicide with a high effective postemergence herbicidal activity. In particular, the unicellular green photosynthetic algae Chlamydomonas reinhardtii was immobilised on a paper substrate soaked with an agar thin film and placed in a glass optical measurement cell, obtaining a totally environmental-friendly device. Nanoencapsulated-atrazine was detected by following the variable fluorescence (1-VJ) parameter, which decreased inversely proportional to the herbicide concentrations, in a range between 0.5 and 200 nM, indicating a linear relationship in the measured dose-response curves and a detection limit of 4 pM. Interference studies resulted in a very slight interference in presence of 0.5 ppm copper and 10 ppb arsenic at safety limits, as well as a slight matrix effect and a satisfactory recovery value of 96 ± 5 % for 75 nM nanoencapsulated-atrazine in tap water. Stability studies were also performed obtaining a good storage stability up to 3 weeks. Results demonstrated the suitability of the proposed paper-based optical biosensor as a valid support in smart agriculture for on site, environmentally friendly, cost effective and sensitive nanoencapsulated-atrazine analysis
Keywords: Paper-based algal biosensor; Chlamydomonas reinhardtii; Chlorophyll fluorescence; Nanoencapsulated-atrazine; Sustainable agriculture